Experimental Study of Dynamic Characteristics of Tailings With Different Reconsolidation Degrees After Liquefaction - Wang, Wensong; Cao, Guansen; Li, Ye; Zhou, Yuxi; Lu, Ting; Wang, Ya; Zheng, Binbin (Frontiers in Earth Science, 2022)
The construction period of most tailings ponds generally lasts for more than ten years or even decades. During this period, it may be affected by more than one earthquake and is often subjected to vibrations generated by mining activities. The tailings liquefied by earthquake or vibration may experience dynamic loads again. Due to the low permeability of tailings, the reconsolidation process of tailings after liquefaction is prolonged. Therefore, changes in the nature of the tailings caused by the previous earthquake will affect the performance of the tailings dam in the subsequent earthquake. Dynamic triaxial tests and bending element tests were conducted on two kinds of tailings from a copper mine in southwest China to study this process. The tailings specimens will undergo two consolidation processes and subsequent cyclic loads during the test. The influence of reconsolidation degree, confining pressure, and particle size on the dynamic characteristics and wave velocity of the tailings after liquefaction under cyclic loading was measured. The results show that the reconsolidation degree significantly affects on the trend of the excess pore water pressure ratio changing with the increase of the cycle number of loads. The reconsolidation process after liquefaction of tailings will improve its liquefaction resistance. The relationship between the ratio of the cycle number of liquefaction after reconsolidation to the cycle number of first liquefaction and the reconsolidation degree is proposed. In the entire experimental process, the shear wave velocity of the tailings gradually decreases when applying cyclic load and gradually increases during the consolidation process, including the first consolidation before cyclic loading and reconsolidation after liquefaction. The research results are of great significance to the safe disposal of tailings, especially those in earthquake-prone areas.